Establishment of the 1st International Genetic Reference Panel for Factor V Leiden, human gDNA - Gray, Elaine; Hawkins, J. Ross; Morrison, Marion; Hawkins, Malcolm; Byrne, Ed; Kitchen, Steve; Jennings, Ian; Makris, Mike; Preston, F. Eric; Metcalfe, Paul (Thrombosis and Haemostasis, 2006)
Forty-one laboratories participated in an international collaborative study to assess the suitability of a panel of three genomic DNA samples as the 1st International Genetic Reference Panel for the Factor V Leiden (FVL) variant.The code numbers of the materials were 03/254 (FV wild type), 03/260 (FVL homozygote) and 03/248 (FVL heterozygote).The participants evaluated the panel against their in-house controls which were known patient samples and commercial controls. In total, 859 genotype tests were carried out on the panel, with an error rate of 0.7%.The errors were not related to specific samples of the panel or to any specific techniques.The findings of this study have indicated that this panel is suitable to be used as a reference material for genotyping of factor V Leiden. It was therefore recommended that the three genomic DNA samples be established as the 1st International Genetic Reference Panel for Factor V Leiden, Human gDNA, 04/224. This recommendation was approved by the Scientific and Standardization Committee (SSC) of the ISTH (International Society on Thrombosis and Haemostasis) in June 2004 and the Expert Committee on Biological Standardization (ECBS) of theWorld Health Organization (WHO) in November 2004.
Keywords: Factor V Leiden; genetic reference materials; genomic DNA; in vitro diagnostics